Reactive Oxygen Species: A Breath of Life or Death? - Fruehauf, John P.; Meyskens, Frank L. (Clinical cancer research, 2007)
New insights into cancer cell–specific biological pathways are urgently needed to promote development of rationally targeted therapeutics. Reactive oxygen species (ROS) and their role in cancer cell response to growth factor signaling and hypoxia are emerging as verdant areas of exploration on the road to discovering cancer's Achilles heel. One of the distinguishing and near-universal hallmarks of cancer growth is hypoxia. Unregulated cellular proliferation leads to formation of cellular masses that extend beyond the resting vasculature, resulting in oxygen and nutrient deprivation. The resulting hypoxia triggers a number of critical adaptations that enable cancer cell survival, including apoptosis suppression, altered glucose metabolism, and an angiogenic phenotype. Ironically, recent investigations suggest that oxygen depletion stimulates mitochondria to elaborate increased ROS, with subsequent activation of signaling pathways, such as hypoxia inducible factor 1α, that promote cancer cell survival and tumor growth. Because mitochondria are key organelles involved in chemotherapy-induced apoptosis induction, the relationship between mitochondria, ROS signaling, and activation of survival pathways under hypoxic conditions has been the subject of increased study. Insights into mechanisms involved in ROS signaling may offer novel avenues to facilitate discovery of cancer-specific therapies. Preclinical and clinical evaluation of agents that modify ROS signaling in cancer offers a novel avenue for intervention. This review will cover recent work in ROS-mediated signaling in cancer cells and its potential as a target for developmental therapeutics.